Barometrische Höhenbestimmungen auf dem grönländischen Indlandeis bei der internationalen glaziologischen Grönlandexpedition (EGIG) 1959. - Gerke, Karl (Meddelelser om Grønland, 1969)
In the course of the EG I G summer campaign of 1959, the geodesy teams carried out tellurometric measurements as well as geodetic levellings, and the atmospheric pressure was currently gauged for barometric determinations of altitude. The instruments used were aneroid barometers, hypsometers, and various makes of psychrometers. The measurements were taken in the east-west profile between A 14 and Cecilia Nunatak, and in the north-south profile from T 100 to T 132, either by the parallel or the overtake method. The observations were analyzed in the Institute of Applied Geodesy, Dept. II of the German Geodetic Research Institute in Frankfurt/Main ; but, regrettably, airpressure registrations of fixed points had to be dispensed with in the process. However, in view of arctic conditions, the results can be claimed to be good, and they bid fair for further barometric levellings lo be gained in future expeditions.